Reports of the Task Forces on Governance, Transparency Participation and Environmental Impact Assessment and Urban Environmental Issues - Planning Commission (Planning Commission, 2007)
The Government of India's Planning Commission convened a Task Force to assess and improve governance in the Environment and Forest sector for the Eleventh Five-Year Plan (2007-2012). The report emphasizes the need for integrated, participatory, and transparent governance to address urban environmental issues and improve Environmental Impact Assessment (EIA) processes. The Task Force's report underscores the critical need for comprehensive reforms in governance, aimed at fostering collaboration among various sectors. The recommendations proposed will help address the complex intersection between development, environmental conservation, and social equity, contributing to a more sustainable future for India.
In the Environment and Forests Sector for the Eleventh Five Year Plan (2007-2012)
Government of India Planning Commission
Keywords: Public Accountability; Expert Committee Involvement; Phased Public Hearings; Length of EIAs; Environmental Appellate Authority; Heritage Conservation; Regulation of Industry Activities; Post-Implementation Monitoring; Restoration Initiatives; Horticultural Programs